Problemy teorii nauczania i uczenia się literatury rosyjskiej i radzieckiej w Polsce Ludowej = Problems of theory in teaching and learning Russian and Soviet literature in the Polish People's Republic - Piotrowski, Władysław (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The author of the artide treats at length of problems of teaching Russian and Soviet literature in the Polish People's Republic and analyses the usefulness of these scientific formulations for the didactics of Polish literature.
Keywords: literatura rosyjska; literatura radziecka; nauczanie; Polska Rzeczpospolita Ludowa